Pelaksanaan Keselamatan Pasien Melalui Lima Momen Cuci Tangan Sebagai Perlindungan Hak Pasien - Maria Ariani Wijaya; A Widanti S; Hartanto Hartanto (Universitas Katolik Soegijapranata Semarang, 2018)
Healthcare-Associated Infections (HAIs) is one of the risks that threaten patient safety. HAIs causing harms to the patient's family and the hospital. Five Moments Hand Hygiene is one of the safeguards to against the risk of infection transmission. However, the compliance of hand washing in Indonesia is not maximal yet.This research is conduct to knowing the regulations of Five Moments Hand Hygiene implementation, obtaining an overview of its implementation and finding the support and inhibiting factors at St. Elisabeth Hospital. The research was conducted by using juridical-empirical approach. The object of this research is the nurse Five Moments Hand Hygiene behaviors at St. Elisabeth Hospital Inpatient Installation.The results shows the legal basis for the implementation of the Five Moments Hand Hygiene in Indonesia is Health Ministry’s Regulation No. 11/2017 on Patient Safety and Health Ministry’s Regulation No. 27/2017 on Guidelines for Infection Prevention and Control at Health Service Facilities. A hand washing compliance of healthcare workers in St. Elisabeth Hospital in 2017 reached 90%. The Director of the Hospital has fulfilled his obligations establishing the Hand Hygiene Guidelines. Supporting factors include availability of facilities and management support. The inhibiting factor is the nurse workload, poor understanding, and the demands of efficiency. Administrative sanctions may be provided for health workers who are not compliant with the SOP.